(Non)automaticity of ritualized behavior - Niczyporuk, Aneta (Religion, brain & behavior, 2022)
Ritualized behavior has been characterized as rigid and goal-demoted. According to Boyer and Liénard (2006), these features ensure that ritualized behavior is non-automatic, enabling it to reduce anxiety. At the same time, non-automatic behavior has been characterized as conscious, effortful, controlled, and slow. As shown in the article, however, none of the non-automaticity features follow from the features of ritualized behavior. Indeed, the rigidity of ritualized behavior should lead to it being automatized. Moreover, it is not non-automaticity as such but conscious preoccupation with ritualized behavior that is likely to decrease anxiety. The consequences of ritualized behavior's automaticity for Boyer and Liénard's theory are discussed. Additionally, there are reviewed available tools for ritualized behavior's automaticity measurement.